THE TAXATION OF EMPLOYEE REVENUE FROM THE FRINGE BENEFITS - Brejdak, Paulina (Review of European and Comparative Law, 2018)
The article presents the issues taxation of employee revenue from the fringe benefits by Personal Income Tax. On the one hand, the employee fringe benefits are identified with a defined benefit and on the other with a non-monetary incentive system. However, the benefits give rise to many doubts and controversies. The reasons for this are the lack of legal definition and the lack of their legal directory. Therefore, the views of the judiciary and decisions of tax authorities indicate for example what can be classified fringe benefits.